Urban microzonation and territorial development: the case of Puerto Bolivar in Ecuador - Berrú, Juan C. (2017)
Rural environmental microzonation is a way to plan the land use within particular urban area, based on the precepts of sustainable development, it becomes important in developing countries where land use planning is essential. There are several ways and tools to carry out such plans, the choice of methodology will determine the success or failure of micro-zoning, so the choosing and applying techniques and tools for this are the main concern when planning begins. Procedures based on three phases arise in this review, such as preparation phase, diagnostic phase and proposal phase. Tools such as use of drones, establishments of orthophoto, GIS development, participatory techniques, scene construction, among others are exposed. It is showed the case of Puerto Bolivar in Ecuador, whose population settlement stands at seaport, accompanied of the high tourism potential and economic movement.